Inclusive Dentistry faculties. State of the art in Latin America - Grandas Ramírez, Ángela Liliana (2021)
People with disabilities are a vulnerable and excluded population from their rights such as admission, permanence and graduation from higher education, especially from in Latin American dental schools. The objective of this review is to review the literature on educational inclusion in Latin American dental schools. A review of the national and Latin American literature was carried out on the concepts of disability, inclusive education and undergraduate dentistry using primary and secondary sources; among which, books, thesis and Medline, SciELO, Pubmed, Lilacs, Dialnet and Redalyc databases were consulted. It was concluded that dental schools are in default and in debt to people with (dis) ability in Latin America due to the dynamics of higher education that continue to perpetuate the exclusion or discrimination of people with disabilities in undergraduate dentistry.